Analisa Ekonomi Penggalian Overburden dengan Menggunakan Metode Penggaruan Dibandingkan dengan Metode Peledakan pada Penambangan Batubara PT Madhani Talatah Nusantara Site Gendang Timburu Kotabaru Kalimantan Selatan - Fitri Desri Yeni; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Madhani Talatah Nusantara Company Site 037C Gendang Timburu is a contractor in the mining concession PKP2B Kalimantan Energi Lestari Company were located in Gendang Timburu village, Durian River District, Kotabaru, South Kalimantan Province. The implementation of mining activities requires for good planning, with the aim of providing a large profit for the company. Mining equipments productivity are the main thing that plays a role in supporting the company's production. Mining activities are carried out by blasting and ripping processes to achieve production targets. Among the excavation methods have differences in productivity and economy. So based on the background above, the research is conducted with the aim of seeing the technical costs differences in the of using both of the method. From the results of the study, it was found that in the ripping activitis using of D9R bulldozer type heavy equipment, the cost of using Liebher R-9250 hydraulic excavator was obtained with a large operating cost in the rock grading activity of Rp. 7.299,90/ bcm with total profits after revenue reduction namely Rp. 22.437,10/bcm. Whereas by using the blasting method with the type MD6290 and using a loading device, namely the hydraulic excavator R-9250, the operational costs of Rp 7.508,68/bcm with a profit of Rp. 21.113,32/bcm.. Keywords: Produktifitas, Ripping, Blasting, Economi, Coal.